2019
DOI: 10.1021/acsomega.9b02064
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Magnetic Properties of the KCu(IO3)3 Compound with [CuO5] Chains

Abstract: The new quaternary iodate KCu(IO3)3 has been prepared by hydrothermal synthesis. KCu(IO3)3 crystallizes in the monoclinic space group P21/n with unit cell parameters a = 9.8143(4) Å, b = 8.2265(4) Å, c = 10.8584(5) Å, β = 91.077(2)°, and z = 4. The crystals are light blue and translucent. There are three main building units making up the crystal structure: [KO10] irregular polyhedra, [CuO6] distorted octahedra, and [IO3] trigonal pyramids. The Jahn–Teller elongated [CuO6] octahedra connect to each other via co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…However, bending modes are also expected in the range 300−450 cm −1 . 24,25 The rather different effect of temperature on the modes is due to the different mechanisms of anharmonicity that collective phonon vibrations and local modes are experiencing. A collective optical vibration can decay into pairs of acoustic modes based on the anharmonicity of the lattice potential.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, bending modes are also expected in the range 300−450 cm −1 . 24,25 The rather different effect of temperature on the modes is due to the different mechanisms of anharmonicity that collective phonon vibrations and local modes are experiencing. A collective optical vibration can decay into pairs of acoustic modes based on the anharmonicity of the lattice potential.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The Cu 2+ ion possesses a partially filled d -orbital and usually occupies a distorted octahedral CuO 6 coordination geometry; hence, the combination of copper cations with iodate groups is expected to form novel structures with various connection fashion of CuO 6 units, and may further afford interesting magnetic properties. As far, only seven Cu-containing quaternary iodates, NaCu(IO 3 ) 3 (Sen Gupta et al, 1987), AgCu(IO 3 ) 3 (Wang et al, 2017), KCu(IO) 3 (Mitoudi-Vagourdi et al, 2019), and Ln Cu(IO 3 ) 5 ( Ln = La, Ce, Pr, and Nd) (Geng et al, 2022), have been reported. In this study, a new Cu-containing quaternary iodate, namely, Ba 2 Cu(IO 3 ) 6 , has been synthesized.…”
Section: Introductionmentioning
confidence: 99%
“…However, iodates for magnetic properties have rarely been reported. In particular, none of the magnetic iodate fluorides has been synthesized and reported yet till now. Here, we first report two new magnetic iodate fluorides MIO 3 F (M = Co 1 and Ni 2 ) by a hydrothermal method with interesting magnetic properties.…”
Section: Introductionmentioning
confidence: 99%